A atuação de Minas Gerais na agenda de mudança do clima - Campos, Letícia Capistrano (2023)
The objective of the work is to analyze the performance of the government of Minas Gerais in the climate change agenda. The theoretical foundation, firstly, the work correlates the 1988 Constitution with the powers of the States, identifying that the execution of public policies on climate change can be carried out both by the Federal Government and by subnational entities. Next, the work presents bibliography related to the cycle of the public policy process and concepts related to climate change. It also presents literature on public policy councils. The nature of the research is qualitative, descriptive, documentary and participatory. The analysis of Minas Gerais' performance went through the cycle of the public policy process on climate change in Brazil and, later, specifically in Minas Gerais. The work, based on this, analyzes Minas Gerais' instruments for the climate agenda. The first instrument are the participatory bodies for the topic of climate change, the Minas Gerais Climate Change Forum - FEMC and the Energy and Climate Change Chamber - CEM of the State Council for Environmental Policies, which have similar competences and did not produce results in the period analyzed. The second instruments analyzed are the Minas Gerais Energy and Climate Change Plan - PLAC and the State Climate Action Plan - PEMC, which replaced it, including the presentation of the Inventories of Anthropogenic Emissions and Removals of Greenhouse Gases - 2014 and 2022. It is comparison of the plans was made, identifying similarity in 68% of the actions and presenting a failure in monitoring. The last instrument is the participation of the State of Minas Gerais in events related to the topic. Finally, the dissertation presents work proposals that aim to contribute to the advancement of climate policy in Minas Gerais, which include the amendment of the FEMC and CEM, the institution of a State Climate Change Policy determined by law, changes to the PLAC and inclusion of actions to mitigate and adapt to the effects of climate change in the State's environmental licensing processes.